CRISPR-drug combinatorial screening identifies effective combination treatments for MTAP-deleted cancer - Knoll, Nikola; Masser, Sarah; Bordas, Blanka; Ebright, Richard Y.; Li, Guangyan; Kesar, Devishi; Destefanis, Eliana; Kania, Nicholas; Rodriguez, Diego J.; Jen, Jayu; Zagar, Sydney E.; Mensah, Caleb; et al. (Cancer research, 2025)
Cyclin-dependent kinase inhibitor 2A (CDKN2A)/methyl-thioadenosine phosphorylase (MTAP) codeletion occurs frequently in non–small cell lung cancer and other solid tumors, including glioblastoma and pancreatic ductal adenocarcinoma. Lung cancer remains the leading cause of cancer-related mortality, and fewer than 15% of patients with glioblastoma or pancreatic cancer survive 5 years, underscoring the need for more effective therapies. Protein arginine methyltransferase 5 (PRMT5) is a synthetic-lethal dependency in MTAP-null tumors and an attractive therapeutic target for CDKN2A/MTAP-deleted cancers. A new revolutionary class of inhibitors, referred to as methylthioadenosine (MTA)-co-operative PRMT5 inhibitors (PRMT5i), has shown promising results in ongoing early-phase clinical trials. Nonetheless, effective cancer treatment typically requires therapeutic combinations to improve response rates and defeat emergent resistant clones. Thus, we sought to determine whether perturbation of other pathways could improve the efficacy of MTA-cooperative PRMT5is (MTAC-PRMT5i). Using a paralog and single gene targeting CRISPR library, we screened MTAP-deleted cancers in the presence or absence of MTAC-PRMT5is. Loss of several genes sensitized cells to PRMT5 inhibition, including members of the MAPK pathway. Chemical inhibition of MAPK pathway members using KRAS, MEK, ERK, and RAF inhibitors synergized with PRMT5 inhibition to kill CDKN2A/MTAP-null, RAS-active tumors. Furthermore, MTAC-PRMT5is combined with either KRAS or RAF inhibitors led to complete responses in vivo, emphasizing the potential benefit for patients. Lastly, cell lines resistant to KRAS inhibition were not resistant to MTAC-PRMT5is and vice versa, suggesting noncross-reactive mechanisms of resistance. Overall, this study identifies therapeutic combinations with MTAC-PRMT5is that may offer significant benefits to patients. Significance: Combining PRMT5 and MAPK pathway inhibitors leads to complete, durable responses in lung cancer models, providing an effective therapeutic strategy for the 4-5% of cancer patients harboring CDKN2A/MTAP deletion and MAPK alterations.
Gesehen am 17.02.2026